Removal of Cr and Zn using AgNPs / TiO2 nanocatalyst / Abdul Muhaimin Abd Jalil and Norain Isa - Abd Jalil, Abdul Muhaimin; Isa, Norain (2020)
Presently, water pollution is increasing by years. Water pollution is occur when there is pollutant or foreign substance contain in the water that decrease the quality of water and become toxic to living organism. One of the major causes that lead to water pollution are heavy metals. Heavy metals is the toxic substance even though at low concentration that can cause adverse effect. The objective of this research are to synthesis and characterize of titanium dioxide nanotubes (TNTs) decorated with silver nanoparticles (AgNPs) and to evaluate the removal of zinc and chromium ions by using the TNTs / AgNPs catalyst with different contact time and initial concentration of Cr and Zn ions. In this research, the TNTs were prepared by using anodisation process at constant 60 V for 20 minutes and by using EG / NH4F / K2CO3 as electrolyte. Besides, the AgNPs were prepared by using salt reduction method with chemicals AgNO3, K. brevifolia extract and NaOH. Next, the TNTs / AgNPs were prepared by using wet impregnation method. Lastly, the removal of chromium and zinc ions were remove by putting the TNTs / AgNPs into each different concentrations which are 5 ppm and 10 ppm. Furthermore, the characterization of the, TNTs, AgNPs and TNTs / AgNPs were done by using Field Emission Scanning Electron Microscopy (FESEM), and Energy Dispersive X-ray Analysis (EDX) and for zinc and chromium ion removal were analysing it by using Inductively Coupled Plasma - Optical Emission Spectrometry (ICP-OES). From the result obtained, TNTs / AgNPs has high efficiency for the removal of Zn ions since the percentage removal of 5 ppm and 10 ppm were 90.81% and 37.16% for Zn ions while percentage removal of 5 ppm for Cr ions was 9.53% respectively. Apart from that, the performance of Zn ions removal by using TNTs / AgNPs are better compared to Cr ions removal under visible light condition.